2009
DOI: 10.1007/s10295-009-0671-3
|View full text |Cite
|
Sign up to set email alerts
|

A thermostable phytase from Bacillus sp. MD2: cloning, expression and high-level production in Escherichia coli

Abstract: Phytase is used as a feed additive for degradation of antinutritional phytate, and the enzyme is desired to be highly thermostable for it to withstand feed formulation conditions. A Bacillus sp. MD2 showing phytase activity was isolated, and the phytase encoding gene was cloned and expressed in Escherichia coli. The recombinant phytase exhibited high stability at temperatures up to 100 degrees C. A higher enzyme activity was obtained when the gene expression was done in the presence of calcium chloride. Produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 45 publications
1
27
2
Order By: Relevance
“…Similar to the phytases previously characterized from Bacillus species [29,[31][32][33], the PHY US573 showed dependence toward calcium for its catalytic activity. Increasing the concentration of this metal ion enhanced the enzyme activity, which attains its maximal level in the presence of 1 mM CaCl 2 .…”
Section: Calcium Requirement For Phy Us573 Activitymentioning
confidence: 71%
See 3 more Smart Citations
“…Similar to the phytases previously characterized from Bacillus species [29,[31][32][33], the PHY US573 showed dependence toward calcium for its catalytic activity. Increasing the concentration of this metal ion enhanced the enzyme activity, which attains its maximal level in the presence of 1 mM CaCl 2 .…”
Section: Calcium Requirement For Phy Us573 Activitymentioning
confidence: 71%
“…This temperature was superior to that of the phytases purified from B. subtilis VTTE 68013 [27] and B. subtilis US417 [25], but comparable to those produced by B. amyloliquefaciens DS11 and Bacillus sp. MD2 which have been reported to be optimally active at 70 • C and 67-73 • C, respectively [29,31]. Study of the effect of temperature on the activity of Ronozyme PL and Natuphos showed that the optimum of these commercial enzymes was 55 • C (Fig.…”
Section: Effect Of Temperature and Ph On Phy Us573 Activitymentioning
confidence: 94%
See 2 more Smart Citations
“…Although the cell membrane and cell wall of archeons and bacteria are significantly different, the signal peptides from these organisms are significantly similar consisting of three regions: an N-region followed by a hydrophobic H-region and a carboxyl terminal C-region, which contains a signal peptidase cleavage site [24,25]. We have previously produced Tk1884, an α-amylase from hyperthermophilic archaeon T. kodakarensis, with the native signal sequence in E. coli and demonstrated that signal peptidase of the host cleaved the signal sequence of the archaeal origin and the mature protein was secreted in the extracellular medium [22].…”
Section: Discussionmentioning
confidence: 99%